Biocarvões e hidrocarvões impregnados com ferro para remoção de sulfeto de hidrogênio no refino do biogás - Montaño, Mayerlin Edith Acuña (2023)
Biogas is a promising source of renewable energy. However, its use is conditioned by the presence of contaminants that are highly toxic to the environment and health, as well as increasing maintenance costs. Hydrogen sulphide (H2S) is the most dangerous, toxic and corrosive contaminant present in biogas and therefore its safe and efficient removal is essential for any energy application. The aim of this study is to evaluate two biosorbents in the desulphurization of synthetic biogas: commercial activated carbon (biochar) subjected to heat treatment in the presence of iron(III) species, and hydrocarbon produced from the hydrothermal combustion of sewage sludge and a residual source containing iron and zinc. This research involved four stages: (i) preparation of the biosorbents, (ii) wet impregnation, (iii) characterization of the biosorbents and (iv) evaluation of the removal efficiency. The desulphurization tests were carried out in a static system (batch), providing an economical and effective approach to simulate real operating conditions. H2Sadsorption was monitored over time using gas chromatography with thermal conductivity detector (GC/TCD). With regard to the results of the materials, the biochar heat-treated in the absence of iron (C100 and C300) showed the lowest H2S adsorption capacities of 31.2 and 49.2 mgH2S g-1, respectively. However, the iron-impregnated materials (C300Fe, C500Fe and C700Fe) showed more effective desulphurization capacities of 86.4, 78.9 and 78.3 mgH2S g-1, respectively. Thus, the C300Fe material stood out as the most technically viable, achieving approximately 74% higher H2S removal compared to the unmodified material (C100), and showed recycling capacity, with deactivation of the sites of 20 to 30% after three cycles. The high concentration of iron species on its surface seems to have compensated for the loss of specific area. The pseudo-first order, pseudo-second order and Bangham kinetic models were used to evaluate adsorption. The pseudo-first order model was the most suitable for describing the process, suggesting that adsorption was preferentially governed by physisorption. As for the hydrocarbons, they reached adsorption capacities in the range of 40.0 to 61.8 mgH2S g-1 and compared to the results obtained with commercial activated carbon, these were significant results, since commercial activated carbon reached 31.2 mgH2S g-1. The data obtained fitted the pseudo-second order model, indicating a chemisorption process. Both materials showed promising results for contributing to innovations in the bioenergy and wastewater utilization sectors.